Legal Framework for Protecting the Right to Private Life in the Digital Space: The Extent to which Jordanian Constitution and legislation Takes into Account International Requirements - Al-Billeh, Tareq (Revista de Investigações Constitucionais, 2024)
The article analyzes the legal framework for protecting the right to private life in the digital space and strengthening the constitutional rights stipulated in the Jordanian Constitution, by regulating the right to private life in the digital space, protecting personal data in light of the ease of collecting, retaining and processing it, and preventing infringement on the right of citizens to protect their personal data and privacy as stipulated in the Jordanian Constitution and relevant legislation. The article aims to find a legal framework that balances the rights of citizens to protect their personal data, and allowing data and information to be processed and preserved in the digital space, as well as the extent to which the Jordanian legislator takes into account international requirements regarding the protection of the right to private life in the digital environment. The study reached several conclusions and recommendations, the most important of which is the need to develop legal legislation to regulate the mechanism of saving and processing personal data within clear restrictions and obligations. In addition, it is necessary to develop legislation to ensure the safety of digital space and support its stability, and define the obligations imposed on those responsible for personal data, as well as the punishments and penalties imposed on persons who violate the legislation that regulate the right to privacy, taking into account international requirements.